A new ground motion intensity measure for short period reinforced concrete structures subjected to near-fault pulse-like ground motions - Durucan, Cengizhan; Sahin, Humeyra; Durucan, Ayse Rusen (Taylor & Francis Inc, 2023)
This study is aimed at developing a new ground motion (GM) intensity measure (IM) based on: (i) the shape of the response spectrum and (ii) spectral acceleration at the fundamental elastic period of the structure, Sa(T1). The proposed GM-IM is developed mainly for short period reinforced concrete (RC) structures subjected to near-fault (NF) pulse-like GM records. The main parameter used in the development of the proposed IM is the ratio of peak ground acceleration (PGA) to peak ground velocity (PGV) of a ground motion record. The proposed IM displayed an improved performance among the other evaluated IMs.
Keywords: Peak ground acceleration; peak ground velocity; response spectrum shape